Leadership Role in the Management of Islamic Educational Institutions in Mts Al Wasliyah 18 Tembung - Siahaan, Amiruddin; Riyadi, Ahmad; Fadilah, Aisyah; Azzahra Lubis, Fatimah; Qodri, Laila; Akmalia, Riski (Jurnal Media Informatika, 2024)
The role of leadership in the management of Islamic educational institutions is very crucial to achieving the institution's vision and mission. Effective leaders not only act as directors, but also as inspirers and motivators for all staff and students. Good leadership is able to create a conducive environment for learning and teaching, as well as ensuring that Islamic values are integrated in all aspects of education. In addition, leaders must have strong managerial skills to manage resources efficiently, improve the quality of education, and overcome various challenges that may arise. Strong and visionary leadership is the key to the success of Islamic educational institutions. In this research we used qualitative research methods with valid data in the form of documentation. The conclusion of this research is that the principal is able to carry out his role well as the highest leader in the madrasah he leads.